2018
DOI: 10.1039/c8ra03266a
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to prepare tussah/Bombyx mori silk fibroin-based films

Abstract: The possibility of using silk fibroin in biomaterials for tissue engineering is a subject of broad interest. In this study, Bombyx mori/tussah silk fibroin (BSF/TSF) blend films were prepared by solution casting using CaCl 2 / formic acid as a co-solvent and water as a rinse solvent. The morphology, crystallinity, thermal resistance, mechanical properties and water contact angle of the blend films as well as the biocompatibility were investigated. The BSF/TSF blend films displayed a smooth surface and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC2 manufacturing chain [33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC2 manufacturing chain [33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC 2 manufacturing chain [33][34][35][36][37] [35][36][37]. However, Zhang et al previously reported on the influence of dissolution of silk fibroin in FA/CaCl 2 on the molecular weight ratio and concluded that in comparison to common dissolution methods facilitating LiBr, CaCl 2 +EtOH, Ca(NO 3 ) 2 +MeHO or LiSCN, among others, the FA/CaCl 2 solvent rather showed decreased alterations in molecular weight [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations